1995
DOI: 10.1111/j.1399-3011.1995.tb01055.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of indolicidin, a tryptophan‐rich antimicrobial peptide from bovine neutrophils *

Abstract: Indolicidin, a novel tryptophan‐rich microbicidal tridecapeptide amide isolated originally from granules of bovine neutrophils, has been prepared by optimized manual and automated protocols of stepwise solid‐phase synthesis with Nα‐9‐fluorenylmethyloxycarbonyl (Fmoc) amino acid derivatives. Both standard polystyrene (PS) and polyethylene glycol‐polystyrene (PEG‐PS) graft supports were used in combination with handles that provide C‐terminal peptide amides: 5‐(4‐Fmoc‐aminomethyl‐3,5‐dimethoxyphenoxy)valeric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The experiments listed above have also been used to study the antibacterial activity of natural and synthetic peptides. For example, the antibacterial activity of peptides such as LL-37, various defensins, indolicidin, and cecropins have all been studied using broth dilution, radial diffusion, hemolysis, NPN uptake, and ONPG influx assays. , …”
Section: Systems For Studying Membrane Permeabilizing Peptidesmentioning
confidence: 99%
“…The experiments listed above have also been used to study the antibacterial activity of natural and synthetic peptides. For example, the antibacterial activity of peptides such as LL-37, various defensins, indolicidin, and cecropins have all been studied using broth dilution, radial diffusion, hemolysis, NPN uptake, and ONPG influx assays. , …”
Section: Systems For Studying Membrane Permeabilizing Peptidesmentioning
confidence: 99%
“…Because of Bill Wimley's work on leakage from vesicles induced by human defensins, Mike Selsted suggested that our two labs collaborate further on mechanisms of action of antimicrobial peptides. Importantly, his lab had sufficient financial resources to recruit two new postdocs to work on defensins and a novel 13AA peptide, indolicidin, that Mike had discovered (133). I had met Alex Ladokhin and Kalina Hristova at the 1994 Biophysical Society meeting in New Orleans.…”
Section: Fruits Of Collaborationmentioning
confidence: 99%
“…Indolicidinbelongs to the family of cathelicidin AMPs. It was first discovered in bovine as tridecapeptide (13 amino acid long) amide from neutrophils showing bactericidal effect (Selsted et al, 1992) including its action on Staphylococcus aureus (ABEL et al, 1995). So far, seven protein coding cathelicidin gene have been identified which are traced to single cluster on chromosome 22 (Tomasinsig and Zanetti, 2005).…”
Section: Indolicidinmentioning
confidence: 99%